Respostas

2013-11-27T00:12:18-02:00
4^x - 4 = 4^x / 4^4
3x /81 = 3^x /3^4

4^x / 4^4 - 3^x /3^4 =0

4^x / 4^4 = 3^x /3^4
A ÚNICA SOLUÇÃO  X = 4

comparando .. x= 4
S ( 4)






1 5 1
Txá poxa. Aí sim! ;D
Muito obrigada, NAAAAAAAANDO S2 kkk
2013-11-27T00:18:40-02:00
 2^{-5x+x^2} =  \frac{1}{64}

 2^{-5x+x^2} =  \frac{2^0}{2^6}

 2^6 . 2^{-5x+x^2} =  2^0

 6 -5x+x^2 =  0

x^2 -5x +6 =  0

a = 1
b = -5
c = 6

Raiz:  \frac{-b +-  \sqrt{b^2 - 4.a.c} }{2.a}


x' = 3

x" = 2

3² + 2² = 9 + 4 = 13 =  \sqrt{13}

1 5 1